Biological Therapy in Inflammatory Bowel Disease Patients Partly Restores Intestinal Innate Lymphoid Cell Subtype Equilibrium - Creyns, Brecht; Jacobs, Inge; Verstockt, Bram; Cremer, Jonathan; Ballet, Vera; Vandecasteele, Roselien; Vanuytsel, Tim; Ferrante, Marc; Vermeire, Séverine; Van Assche, Gert; Ceuppens, Jan L.; Breynaert, Christine (Frontiers in Immunology, 2020)
Patients with Crohn’s disease (CD) and ulcerative colitis (UC) suffer from chronic relapsing intestinal inflammation. While many studies focused on adaptive immunity, less is known about the role of innate immune cells in these diseases. Innate lymphoid cells (ILC) are recently identified cells with a high cytokine producing capacity at mucosal barriers. The aim was to study the impact of biological treatment on ILC in CD and UC. Patients initiating anti-TNF, ustekinumab or vedolizumab treatment were prospectively followed up and peripheral and intestinal ILC were determined. In the inflamed gut tissue of patients with IBD we found an increase in ILC1 and in immature NKp44- ILC3, while there was a decrease of mature NKp44+ ILC3 when compared to healthy controls (HC). Similar but less pronounced changes in ILC1 were observed in blood, while circulating NKp44- ILC3 were decreased. Fifteen % of CD patients had NKp44+ ILC3 in blood, and these cells were not detected in blood of HC or UC patients. Therapy with three different biologicals (ustekinumab targeting the IL-12/23 cytokines, anti-tumor necrosis factor and vedolizumab) partly restored intestinal ILC subset equilibrium with a decrease in ILC1 (except for ustekinumab) and an increase in NKp44+ ILC3. Anti-TNF also mobilised more NKp44+ ILC3 in circulation. As ILC1 are pro-inflammatory cells and as NKp44+ ILC3 contribute to homeostasis of intestinal mucosa, the observed effects of biologicals on ILC might contribute to their clinical efficacy.